Synergistic effect of chromium on the mechanical properties and microstructures of spheroidal graphite cast iron - Tshakatumba, Constantin; Ngoy Moise Raphael, Moramess; Tshipeshi Makina, Héritier; Kiswakala Katwebe, Kaki Jospin; Kyungu Mutumba, Dieudonné; Nkulu Wa Ngoie, Guy (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
The fragmentation equipment used in ore’s preparation operations is internally lined with armor whose characteristics require better wear resistance and resilience. The aim of this study was to develop a new generation of high-performance 4% Cr spheroidal graphite (GS) cast iron materials for the manufacture of self-growing shredder lift bars. This typeface was designed in the optic to replace the commonly used white cast iron. The results were used to assess the effect of chromium on the microstructure of the cast iron as well as on its mechanical behavior. It is noted that the presence of chromium leads to the appearance of eutectic carbides and out-of-balance dies. Two types of chromium carbide (Fe,Cr)7C3 and (Fe,Cr)3C precipitate into the matrix and effectively contribute to the improvement of mechanical performances of this material.The quench and tempering heat treatments applied to these materialsled to the following optimum values: impact resistance of 4.8 J/cm2 for the GS 4Cr nuance, 5 J/cm2 for the GS nuance and 0.9 J/cm2 for the 9 cast iron nuance; hardness values of 691, 511 and 509 HV30 were measured respectively for GS 4Cr cast iron, GS cast iron and 9 cast iron treated. The optimal lifetime of each material was estimated at approximately 285 days for treated GS cast iron, 585 days for GS 4Cr cast iron treated and 242 days for normalized cast iron 9.